Provincial electoral districts [1967] - Province of Ontario (Producer) (Province of Ontario, 1967)
An electoral map of the Province of Ontario as of 1967. Legend on the left side of the map divides cities and towns into population brackets. Geographic boundaries, railways, First Nations reserves, provincial parks, and elevations are noted in the legend. Areas highlighted in red are covered in more detail in inset maps. Scale is 1:506,880. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .